INDITEX, a model company in the implementation of sustainable human resource management. (2015) - Mejías, Ana M.; Garrido, Nuria; Pardo, Juan E.
The aim of this paper is to illustrate the sustainable human resource management (SHRM) approach through the application of a theoretical model to INDITEX as an exemplary case study. According to this approach, it is necessary to integrate the human resource policies for sustained business performance and positive employee outcomes of equity, development and well-being. We have applied a qualitative content analysis technique for developing this application of published annual reports of the company. The evolution that this company shows through its public reports (2002-2012) in the corporate social responsibility framework highlights some lessons to understand the importance of focusing on people. This approach is important as a mean to achieve employee satisfaction and commitment, productivity and profits, and human resource sustainability in organisations.